Transcoherent States: Optical States for Maximal Generation of Atomic Coherence - Aaron Z. Goldberg; Aephraim M. Steinberg (PRX Quantum, 2020)
Quantum technologies are built on the power of coherent superposition. Atomic coherence is typically generated from optical coherence, most often via Rabi oscillations. However, canonical coherent states of light create imperfect resources; a fully quantized description of “π/2 pulses” shows that the atomic superpositions generated remain entangled with the light. We show that there are quantum states of light that generate coherent atomic states perfectly, with no residual atom-field entanglement. These states can be found for arbitrarily short times and approach slightly-number-squeezed π/2 pulses in the limit of large intensities; similar ideal states can be found for any (2k+1)π/2 pulses, requiring more number squeezing with increasing k. Moreover, these states can be repeatedly used as “quantum catalysts” to successfully generate coherent atomic states with high probability. From this perspective we identify states that are “more coherent” than coherent states.